2021
DOI: 10.25115/eea.v39i5.4794
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Marketing Strategy for Enterprise Financial Growth

Abstract: The development of marketing strategies has long been engaged in by scientists and practitioners who have written countless algorithms, mechanisms and schemes for the successful development of a marketing strategy. However, in current conditions, all these developments have become obsolete for one main reason: the behaviour of the buyer has radically changed. This reason has again raised the need to develop effective recommendations for the formation of a marketing strategy for the enterprise's financial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Marketing strategies for a product are essential to attracting customers. According to Laburtseva, et al [34], customers no longer take the price of the product as the only criterion for choosing a product as a preferred product. Therefore, in their study on the development of a marketing strategy for enterprise financial growth, it was found that aside from price and quality of product, personal attitude increases.…”
Section: Market Development and Performance Of Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing strategies for a product are essential to attracting customers. According to Laburtseva, et al [34], customers no longer take the price of the product as the only criterion for choosing a product as a preferred product. Therefore, in their study on the development of a marketing strategy for enterprise financial growth, it was found that aside from price and quality of product, personal attitude increases.…”
Section: Market Development and Performance Of Smesmentioning
confidence: 99%
“…Meanwhile, Laburtseva, et al [34] found that customers no longer take the prices of the products as the only criterion to choose a product as a preferred product. However, they noted that aside from price and quality of product, personal attitude is also very critical for market development that will meet customers' needs.…”
Section: Market Development and Performance Of Smes (Profitability Se...mentioning
confidence: 99%